Formação da Nova Geopolítica das Mudanças Climáticas (Sustainability in Debate, 2013)
This paper presents the evolution on climate change negotiations towards a more inclusive andefficient global agreement, and how the main countries position and group themselves, to showthat the geopolitical configuration of climate change has been changed. North-South divergence,settled in terms of development, shaped for a long time the course of negotiations, including thebasis for the structure of the international environmental order of climate change through the“common but differentiated responsibilities” principle. However, the present state of climatenegotiations shows that such North-South division gave place to an assembly of countries definedin terms of spatialization of greenhouse gases emissions. A greater scientific knowledge on thecauses and consequences of climate change, raised by the research and reports published by IPCC,and a shift on the world scenery defined by the power games between great powers are elementsthat help us to investigate a shift on climate change geopolitics. The geopolitics we observe nowadaysopposes the great GHG emitters to countries with expressive and growing emissions, but that arenot able, separately or in small groups, of exerting power enough, at a global level, to alterinternational outcomes.